PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR IPA SISWA SEKOLAH DASAR - Handayani, Sulma; Kartono, Kartono; Halidjah, Siti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study was to analyze the effect of the problem based learning model on the learning outcomes of natural sciencestudents of Class VI Pontianak Elementary School 24 Pontianak Kota and analyze how high the influence of the problem based learning model on the learning outcomes of natural science students of Class VI Pontianak 24 Primary School The research method used was an experimental method in the form of a quasi experimental design, with the experimental design of nonequivalent control group design. The sample selection uses a purposive sampling technique. Based on statistical calculations of the average results of the final test of the experimental class 76.70 and the average of the final test results of the control class 70.37 obtained of 3.561 and  (α = 5% and dk 30 + 31 - 2 = 59) equal to 3,549, because  (3,561)>  (3,549), then Ha is accepted. From the calculation of the effect size (ES), an ES of 0.64 (medium criterion) is obtained. This means that the model of problem-based learning has a moderate effect on the learning outcomes of natural science students of Class VI State Elementary School 24 Pontianak City. Keywords: Effect, Learning Outcomes, Problem Based Learning.